Designing Horticulture Education Game - Khoirul Fikri Shona; Albertus Dwiyoga Widiantoro; Bernardinus Harnadi (Soegijapranata Catholic University, 2019)
Learning about fruit crops can be done by utilizing the gaming media. The purpose of this research is to design a game with a concept of horticulture including planting, caring for, and maintaining fruit trees. This game is packaged in an attractive appearance and resembleing the state of the garden. The game was tested by 43 hortimart visitors the result shows that the game is easy and fun to play so that users will continue to use it but it isn’t influence by age, gender, and usefulness of the game